Rx for structured product labeling three headaches for drug companies to avoid in converting to XML systems. - Dube, Dan
The long term benefits of XML based structured product labelling (SPL) are creating many short-term headaches for drug makers as they scramble to comply with the Food and Drug Administration (FDA) deadline for electronically processing all drug related labeling content.